Air temperature change manifestation at the Zhytomyr territory - L. O. Herasymchuk; R. A. Valerko; I. G. Patseva (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Екологія, 2023)
The territory of cities with a changing environment, a significant density of population, industrial and transport facilities, daily activities that ensure its vital activity and cause significant greenhouse gas emissions, causes a significant contribution to climate change, which is one of the most acute environmental problems of our time.